Is there any real effect of low dimensional morphologies towards light harvesting? a case study of Au-rGO-TiO2 nanocomposites - Melvin, Ambrose A.; Bharad, Pradnya A.; Illath, Kavya; Lawrence, Meenu P.; Gopinath, Chinnakonda S. (Chemistry Select, 2016)
Nanotube and nanosheet morphologies have been celebrated for their electron transport properties. Present work has been explored to exploit the same by combining 1D TiO2 nanotube (1D-TN) with 2D reduced graphene oxide (rGO) along with nano gold for visible light sensitization for photocatalytic H2 generation under one sun condition and visible light (λ≥ 400 nm). Vertical and horizontal electron transport in 1D-TN and rGO, respectively, is combined with the visible light absorption capability of Au nanoparticle. H2 yield (HY) varies between 100 and 655 µmol/g.h with an apparent quantum yield between 0.45 and 3.2 %, respectively, depending on Au/rGO/1D-TN preparation method and reaction conditions. It has been demonstrated that interfacial contact between rGO/1D-TN and Au is crucial for high photocatalytic HY. Preparation method influences charge utilization, and hence HY, to a large extent. Nonetheless, the maximum HY reported in the present work is just comparable to HY reported in literature with the most commonly found spherical morphology, and this leads to a question of, is there any real influence of 1D and/or 2D materials, particularly, towards light harvesting applications?